The Influence of Discipline and Competence on Employee Performance with Motivation as an Intervening Variable in the Organizational Bureau of the Jambi Provincial Secretariat - Tri Wahyu Sidiq, M.; Syeikh, Saiyid; Akbar, Ali (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the influence of Discipline and Competence on Employee Performance with Motivation as an Intervening Variable in the Organizational Bureau of the Jambi Provincial Secretariat. The method used in this study is a descriptive verification and quantitative method. This study was conducted at the Organizational Bureau of the Jambi Provincial Secretariat with a sample of 61 people. This study uses SPSS 26.0 analysis tools. Descriptively, work discipline, competence, motivation and employee performance are perceived to have been going well. Based on the results of the analysis using SPSS 26.0 software that Discipline has a significant and positive effect on motivation, Competence has a significant and positive effect on motivation, Discipline has a significant effect on employee performance, Competence has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, Discipline has a positive and significant effect on employee performance through work motivation and Competence has a significant and positive effect on employee performance through motivation in the Organizational Bureau of the Jambi Provincial Secretariat.